History of Rice Planting Tradition in Belitang Community (1937-1942) - Permadi, Gofo; Susanti, L.R Retno (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2024)
This study discusses how the initial background of the formation of the tradition of planting rice in the Belitang community (1937-1939) and how the development of the tradition of planting rice in the Belitang community (1940-1942). This research uses historical research methods or historical research includes, heuristics, source criticism, interpretation, and historiography. This research uses sociological and anthropological approaches, data collection techniques in this study through observation, literature studies and interviews. The results showed that the beginning of the formation of the tradition of planting rice in the Belitang community occurred in 1937, 1938, and 1939. This is because the Dutch government in power in Belitang implemented ethical political policies, moving residents from Java Island and making irrigation canals. Furthermore, the development of rice planting traisi in the Belitang community in 1940, 1941, and 1942. In 1940 and 1941 there was no perfect way to grow rice, after Japan came to power in 1942, Japan implemented the Kinkyu Shokuryo Taisaku system which updated the agricultural system from tillage to rice planting techniques. In addition, the transmigation community also carries out a kind of ritual honoring the goddess Sri (goddess of rice) when planting rice using sesajen